Dandakaranya in Shanghai: A Transcultural Discussion of City-Zen - Jähnichen, Gisa (Journal of Urban Culture Research, 2018)
The Shanghai Conservatory of Music owns a large collection of ‘Oriental Musical Instruments’ that are exhibited and stored in its museum. Every week, a gamelan class is held in order to promote the collection of instruments. Recently, scenes from the Dandaka forest of the Ramayana were put in a dance performance accompanied by students playing the large Javanese gamelan of the museum. The paper shows how the discussion of global human values as well as the necessity of practicing ensemble playing in a highly competitive cultural environment makes the gamelan class becoming a time space for mental recreation and a playground for social engagement. This paper attempts to discuss the many layers of this specific cultural environment in one of the biggest cities of the world. Special emphasis is given to the creative processes in changing perspectives on dealing with transcultural issues, labels, and emblematic structures in music and dance.